An encounter of two worlds : musical rhythms as a way to shape students’ intercultural competence - Triana Rocha, Sherly Yojana; Castellanos Avila, Liliana Andrea; Cruz Bernal, Daniel Alirio (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (101 páginas) : ilustraciones color, tablas, figuras.